An empirical investigation of the Internet and international trade: The case of Bolivia - Caroline L. Freund; Diana Weinhold (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2000)
This paper builds on Freund and Weinhold (2000) to show that the results of that paper can be applied to the case of Bolivia. We review the implications of the Freund and Weinhold model, emphasizing the effects of the Internet on increasing trade and lessening the effects of historical trading patterns in determining trade flows. Specifically, using a gravity model of trade for 56 countries including Bolivia, we show that the Internet stimulates trade and that Bolivia stands to gain an economically significant benefit from increased Web connectivity. Our results imply that a 10 percent increase in the relative number of web hosts in Bolivia would have led to about 1 percent greater trade in 1998 and 1999. The evidence is consistent with a model in which the internet creates a global exchange for goods, thereby reducing market-specific sunk costs of exporting.
Keywords: 330; internet; gravity model of trade; Bolivia